2017
DOI: 10.1093/dnares/dsx038
|View full text |Cite
|
Sign up to set email alerts
|

Genome re-annotation of the wild strawberry Fragaria vesca using extensive Illumina- and SMRT-based RNA-seq datasets

Abstract: The genome of the wild diploid strawberry species Fragaria vesca, an ideal model system of cultivated strawberry (Fragaria × ananassa, octoploid) and other Rosaceae family crops, was first published in 2011 and followed by a new assembly (Fvb). However, the annotation for Fvb mainly relied on ab initio predictions and included only predicted coding sequences, therefore an improved annotation is highly desirable. Here, a new annotation version named v2.0.a2 was created for the Fvb genome by a pipeline utilizing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
65
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 59 publications
(67 citation statements)
references
References 51 publications
2
65
0
Order By: Relevance
“…The variation in NBS‐LRR gene content between individuals has been assumed to play an important role in the resistance or susceptibility of crops to disease (Tollenaere et al ., ; Wu et al ., ). Furthermore, we found that the largest class of RGA candidates were RLKs, which has been previously reported in other plants, such as wild strawberry and cotton (Chen et al ., ; Li et al ., ). This frequency might be due to a greater diversity of roles of RLK than RLP and NBS‐LRR genes.…”
Section: Discussionmentioning
confidence: 99%
“…The variation in NBS‐LRR gene content between individuals has been assumed to play an important role in the resistance or susceptibility of crops to disease (Tollenaere et al ., ; Wu et al ., ). Furthermore, we found that the largest class of RGA candidates were RLKs, which has been previously reported in other plants, such as wild strawberry and cotton (Chen et al ., ; Li et al ., ). This frequency might be due to a greater diversity of roles of RLK than RLP and NBS‐LRR genes.…”
Section: Discussionmentioning
confidence: 99%
“…The 21nt miR164a mature sequence is located within the first exon, and the SNP (G to A) occurred in its 19 th nucleotide. Based on the prior RNA‐seq data (Li et al ., ), pri‐ FvemiR164A is more abundant in shoot apical meristem (SAM), flower meristem (FM), and receptacle meristem (REM) (Fig. S4a).…”
Section: Resultsmentioning
confidence: 97%
“…The other two genes are named as FveMIR164B and FveMIR164C . According to the previous RNA‐seq data (Li et al ., ), pri‐ FvemiR164A is more abundant in SAM, FM, and receptacle meristem (REM), while pri‐ FvemiR164B is preferentially accumulated in anthers and fruit receptacles, suggesting that they may function in different tissues and developmental processes. FvemiR164c is expressed at a much lower level (Fig.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To date, the i5K Workspace has supported publication of seven insect genomes that were manually curated with Apollo (11)(12)(13)(14)(15)(16)(17). Other projects that have used Apollo include genomes of additional insects (18)(19)(20), human parasites (21)(22)(23), birds (24,25), the sea lamprey (26), plants (27)(28)(29), fungi (30)(31)(32)(33)(34)(35) and a plant pathogenic nematode (36). Projects such as the re-annotation of the whipworm genome by hundreds of high school students in the UK, supported by the Institute for Research in Schools (IRIS) (37), and the curation of 33,044 gene loci in the kiwifruit genome by 93 annotators, are evidence of Apollo's robust support for large dispersed projects.…”
Section: Introductionmentioning
confidence: 99%